Raising public awareness on anthropogenic underwater noise by means of playful activities and serious games - Diviacco, Paolo; Iurcev, Massimiliano (Frontiers in Communication, 2025)
Anthropogenic underwater noise can seriously affect the marine environment and species. Although great progress has been made both from a normative and scientific point of view, public perception of this hazard is very limited. The Noixe project addresses precisely this gap and aims to raise collective awareness of this problem and the role each of us can play in reducing the impact on the environment. This paper describes what we have developed to raise knowledge and awareness of this issue through playful activities and serious games both in live situations and online. The Noixe events are divided into two sections: First, all the concepts needed to understand anthropogenic noise are explained using experiences that anyone can have in their lives. For example, it is possible to explain how noise can make a message contained in an acoustic signal unrecognizable, staging the case of a teacher explaining something to a noisy class. The second moment of a Noixe event is the serious game. Here, in a quiz-like environment, two teams compete against each other to guess a set of sounds that are initially masked by noise. The system we developed makes it possible to gradually reduce the volume of the noise and increase the volume of the sound until it becomes intelligible. The team that identifies more sounds wins. The online version of Noixe is built on a similar workflow but cannot offer all the features of the live events. In particular, it is very difficult to recreate collective experiences such as team games due to possible connectivity issues. This is why we opted for a single user mode. We have found that our approach is very effective in raising awareness on the topic of anthropogenic noise in both live and online settings. This is demonstrated by the fact that practically all Noixe participants decided to join citizen science activities on noise monitoring we later offered them. In this paper we present the technical details of the activities we have developed so that anyone can replicate and improve our work.